Ferns in Sago Malintang Nature Reserve, West Sumatra and their acclimatization in Bogor Botanical Garden - SRI HARTINI (Society for Indonesian Biodiversity, 2006)
Sago Malintang Nature Reserve is one of conservation area in West Sumatra which have some potential plants. Ferns is one group which can be found ini this area, which several of them are attractive and useful. The aims of the research were to inventory ferns in Sago Malintang Nature Reserve and to know the acclimatization process of these species in Bogor Botanical Garden. The method used in this research were explorative method at the place and observation of the growth of living collections in Bogor Botanical Garden. The result showed that there were approximately 17 species of ferns in Sago Malintang Nature Reserve. Bogor Botanical Garden collected 11 species of them. The botanical information of each species is presented in this paper. The acclimatization process of these species in Bogor Botanical Garden has a good condition.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words : ferns, Sago Malintang Nature Reserve, acclimatization, Bogor Botanical Garden